Mobile and Ubiquitous Systems: Computing, Networking, and Services 8th International ICST Conference, MobiQuitous 2011, Copenhagen, Denmark, December 6-9, 2011, Revised Selected Papers - Puiatti, Alessandro; Gu, Tao.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This book constitutes the thoroughly refereed post-conference proceedings of the 8th International ICST Conference on Mobile and Ubiquitous Systems: Computing, Networking, and Services, MobiQuitous 2011, held in Copenhagen, Denmark, in December 2011. The 34 revised full papers presented were carefully reviewed and selected from numerous submissions. They cover a wide range of topics ranging from localization and tracking, search and discovery, classification and profiling, context awareness and architecture, location and activity recognition as well as a best paper session, an industry track, and poster and demo papers.
Localization and Tracking -- Best Paper Session -- Search and Discovery -- Classification and Profiling -- Industry Track -- Poster and Demo -- Wireless Communication and Routing -- Context Awareness and Architecture -- Location and Activity Recognition.
Keywords: Computer science; Computer communication systems; Software engineering; Algorithms; Information storage and retrieval; Artificial intelligence; Computer Science; Computer Communication Networks; Information Systems Applications (incl. Internet).; Artificial Intelligence (incl. Robotics).; Software Engineering; Algorithm Analysis and Problem Complexity; Information Storage and Retrieval; Electronic books